A novel lightweight refractory high-entropy alloy - Wentao Jiang; Tiantian Wang; Xiaohong Wang; Bo Jiang; Ye Wang; Xin Wang; Hongyu Xu; Maoliang Hu; Dongdong Zhu (Journal of Materials Research and Technology)
A novel equiatomic refractory AlNbTiVY high-entropy alloy containing rare earth elements was fabricated by vacuum arc melting. AlNbTiVY alloy possesses a dual-phase structure, consisting of a B2 ordered matrix and an Orthorhombic structured Y2Al second phase. The alloy has a dendritic microstructure with a density of only 5.18 g/cm3. As the testing temperature increases, the compressive yield strength of the alloy gradually decreases from 1104 MPa at room temperature to 321 MPa at 800 °C, with improved deformability and no fracture occurring in the 800 °C environment. Based on the insights of physics, a simple calculation was conducted on the temperature-dependent model of the alloy, and the theoretical application temperature of the alloy was predicted to exceed 600 °C.